2008
DOI: 10.1128/jvi.00456-08
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Vesicular Stomatitis Virus Vector Mediates Postexposure Protection against Sudan Ebola Hemorrhagic Fever in Nonhuman Primates

Abstract: Recombinant vesicular stomatitis virus (VSV) vectors expressing homologous filoviral glycoproteins cancompletely protect rhesus monkeys against Marburg virus when administered after exposure and can partially protect macaques after challenge with Zaire ebolavirus. Here, we administered a VSV vector expressing the Sudan ebolavirus (SEBOV) glycoprotein to four rhesus macaques shortly after exposure to SEBOV. All four animals survived SEBOV challenge, while a control animal that received a nonspecific vector deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 18 publications
3
99
0
1
Order By: Relevance
“…Subsequent studies by the same group showed that rVSV-EBOV (Mayinga strain) protected 50% of rhesus monkeys against EBOV (Kikwit strain) challenge 192 and that an rVSV-SUDV (Boniface strain) vaccine protected 100% of rhesus macaques against homologous SUDV challenge 193 .…”
Section: Vaccine Vectors As Post-exposure Treatmentsmentioning
confidence: 99%
“…Subsequent studies by the same group showed that rVSV-EBOV (Mayinga strain) protected 50% of rhesus monkeys against EBOV (Kikwit strain) challenge 192 and that an rVSV-SUDV (Boniface strain) vaccine protected 100% of rhesus macaques against homologous SUDV challenge 193 .…”
Section: Vaccine Vectors As Post-exposure Treatmentsmentioning
confidence: 99%
“…In the recent past, experimental postexposure treatments for filovirus infections have included hyperimmune equine IgG (9), EBOV-specific human monoclonal IgG antibody (16), wholeblood transfusions from convalescent survivors (8), recombinant IFN (13), recombinant nematode anticoagulant protein C2 (19), recombinant human activated protein C (20,21), recombinant vesicular stomatitis virus vectors (22)(23)(24)(25), siRNAs (26), and phosphorodiamidate morpholino oligomers (27). A summary of these efforts is detailed in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…More important, 50% of cynomolgus macaques were survived if administrated with rVSV-EBOV 20 to 30 minutes after Ebola virus infection (Table 3). 13 Other preclinical studies also demonstrated a rapid and significant protection in NHPs. 12,14,[48][49][50][51][52] The first 3 open-label, uncontrolled, phase I clinical trials of rVSV-EBOV vaccine were conducted in Lambar en e, Kilifi, and Hamburg, respectively, which were designed to assess the safety, and immunogenicity of escalating doses ranging from 3 £ 10 5 to 2 £ 10 7 vp in early 2014 (NCT02283099, NCT02287480, NCT02296983) ( Table 1).…”
Section: Rvsv-ebovmentioning
confidence: 99%
“…Results from pre-clinical trial studies indicated that both humoral and cellular immunity play an essential role in controlling and eliminating virus due to the spiking of Ebola virus envelope GP forms on the surface of mature virions. [12][13][14] The 2014 Ebola epidemic has significantly accelerated the development of Ebola vaccines, 46 clinical trials with Ebola vaccines were launched according to the registration on Clinicaltrial.gov and Pan African Clinical Trials Registry since then (Tables 1 and 2). 15 Different kinds of Ebola vaccines had been developed and evaluated, which can be roughly divided into 3 categories: non-replicative vector-based Ebola vaccines, replicative vector-based Ebola vaccines and others (Fig.…”
Section: Overview Of the Development Of Ebola Vaccinesmentioning
confidence: 99%